Analisis Kemiskinan di Kota Pagar Alam - Bayu Dimas Sanjaya; Syamsurijal A Kadir; Fachrizal Bahri (Department of Development Economics, Universitas Sriwijaya, 2018)
This study aimed to analyze the influence of education level of head of family, number of dependents and asset of head of family on poverty in District of South Pagaralam and North Pagaralam. The data is used in this study are primary data obtained through research directly to the society in November 2016. The method used is a quantitative approach by applying multiple regression models. Based on the research and data processing using multiple regression analysis that education and asset of heads of family have a significant effect on poverty. Meanwhile, head of family number of dependents do not have a significant effect on poverty.